Synthesis, Characterization and Theoretical Investigation of Innovative Charge-transfer Complexes Derived from the N-phenyl 3, 4-selenadiazo Benzophenone Imine (Baghdad Science Journal, 2023)
In the current study, a direct method was used to create a new series of charge-transfer complexes of chemicals. In a good yield, new charge-transfer complexes were produced when different quinones reacted with acetonitrile as solvent in a 1:1 mole ratio with N-phenyl-3,4-selenadiazo benzophenone imine. By using analysis techniques like UV, IR, and 1H, 13C-NMR, every substance was recognized. The analysis's results matched the chemical structures proposed for the synthesized substances. Functional theory of density (DFT) has been used to analyze the molecular structure of the produced Charge-Transfer Complexes, and the energy gap, HOMO surfaces, and LUMO surfaces have all been created throughout the geometry optimization process utilizing the base set of 3–21G geometrical structures. The molecular geometry and contours for compounds with charge-transfer complexes have been evaluated during the process of geometrical optimization. By investigating the interactions between donor and acceptor, we have also been contrasting the energies (HOMO energies) of the chemicals in charge-transfer complexes. For molecules containing charge-transfer complexes, the lower case, electronegativity, ionization potential, electron affinity, and electrophilicity have all been calculated and studied.